Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2004
DOI: 10.1145/985692.985744
|View full text |Cite
|
Sign up to set email alerts
|

The participatory design of a sound and image enhanced daily planner for people with aphasia

Abstract: Aphasia is a cognitive disorder that impairs speech and language. From interviews with aphasic individuals, their caregivers, and speech-language pathologists, the need was identified for a daily planner that allows aphasic users to independently manage their appointments. We used a participatory design approach to develop ESI Planner (the Enhanced with Sound and Images Planner) for use on a PDA and subsequently evaluated it in a lab study. This methodology was used in order to achieve both usable and adoptabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(76 citation statements)
references
References 10 publications
(9 reference statements)
2
71
0
Order By: Relevance
“…Their experiences (including outcome of the project) demonstrated that PD is a viable approach for involving special needs users with cognitive impairments in the design of technology. Similarly promising results have been noted by Moffatt et al (2004) who used PD methods to design a daily planner for people with aphasia.…”
Section: Introductionsupporting
confidence: 53%
“…Their experiences (including outcome of the project) demonstrated that PD is a viable approach for involving special needs users with cognitive impairments in the design of technology. Similarly promising results have been noted by Moffatt et al (2004) who used PD methods to design a daily planner for people with aphasia.…”
Section: Introductionsupporting
confidence: 53%
“…GPRS (General Packet Radio Service) systems, cameras and PDAs are all existing technologies that can be used for this purpose. Developments up to now have focused predominantly on devices to assist in direct communicative exchanges [8].…”
Section: Technology and Tools For People With Aphasiamentioning
confidence: 99%
“…a stylus) and pointing [7]. In addition, tapping interaction has shown to be problematic for those with motoric impairments as it provides no support for targeting [8].…”
Section: Designing For Individuals With Aphasiamentioning
confidence: 99%
“…For instance, Mike Wu, Brian Richards, and Ron Baecker (2004) used PD with a group of six individuals with memory loss (amnesia) to develop a computational tool to help with the problem of disorientation. In another research project, PD was used with people with aphasia in the development of an Enhanced with Sound and Images (ESI) planner for the personal digital assistant (PDA) (Moffatt, McGrenere, Purves, & Klawe, 2004). Julia Galliers, Stephanie Wilson, Abi Roper, Naomi Cocks, Jane Marshall, Sam Muscro, and Tim Pring (2012) also engaged potential users with aphasia, and conducted a series of workshops in which five participants used gestures (rather than spoken or written language) to express ideas about soware and paper game prototypes and to provide evaluations of them.…”
Section: Participatory Design (Pd)mentioning
confidence: 99%